Driving Cycle Analysis for Fuel Economy and Emissions in Kuala Terengganu during Peak Time - Anida, I. N.; Fathonah, A. Z.; Atiq, W. H.; Norbakyah, J. S.; Salisa, A. R. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Number of vehicles grows rapidly in Kuala Terengganu by year. This increment is troubled by the performance of the vehicle regarding pollutants generated. Plug-in hybrid electric vehicles (PHEV) are widely considered to be the most promising vehicles instead of the traditional engine vehicles to reduce fuel consumption and exhaust gas emission. The objectives of this paper are to develop driving cycle of Kuala Terengganu and to analyse the fuel economy and emissions in Kuala Terengganu during peak time. Driving cycle is where PHEV is used as the main apparatus to determine the driving cycle data. In this study, the on-road measurement method is used to collect the data, along with the global positioning system. This technique involves recording speedtime dataset in the real-world driving cycle. Three main methods to identify the best driving cycle are route selection, data collection and data analysis. The data were analysed to get the best driving cycle using a computer program, which is Mathematical Laboratory (MATLAB), along with validated parameters.